2014
DOI: 10.25103/jestr.072.02
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline silicon cells and modules in present photovoltaics

Abstract: Impressive progress in PV technology over the past thirty years is evident from the lowering costs, the rising efficiency and the great improvements in system reliability and yield. Yearly growth rates in the last decade (2003-2013) were on an average higher than 40%, and the global cumulative PV power installed reached 140 GWp in 2013 and photovoltaic power installed in 2013 overcome 30 GWp. The workhorse of present photovoltaics is crystalline silicon technology. Basic principles of photovoltaic cell physics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Cells based on a heterojunction between amorphous and c‐Si have an efficiency exceeding 22% [23]. Some more details about c‐Si cell technology development may be found in [21, 24].…”
Section: Pv Cell and Module Fabricationmentioning
confidence: 99%
“…Cells based on a heterojunction between amorphous and c‐Si have an efficiency exceeding 22% [23]. Some more details about c‐Si cell technology development may be found in [21, 24].…”
Section: Pv Cell and Module Fabricationmentioning
confidence: 99%
“…Experimental research concerning formation and modification of silicon structures, applicable in the photovoltaic industry, aimed at achieving possibly high efficiency of solar energy conversion has been the subject of many scientific discussions [1,2]. Particularly, analysis presented in [3] indicated that there is a necessity of introducing a multi-threaded approach to the solar cells designing process by applying mathematical models including areas, which have not already been taken into consideration, such as full-wave optics, thermal modeling and mechanisms of electric charge transport.…”
Section: Introductionmentioning
confidence: 99%